The semigroup ring of a restriction semigroup with an inverse skeleton - Gomes, Gracinda M. S. (2016)
In this paper we investigate some classes of semigroup rings with respect to (semi)primeness and (semi)primitivity. We do so by extending the techniques developed by Munn in (Proc R Soc Edinbur Sect A 107:175-196, 1987) and (Proc R Soc Edinbur Sect A 115:109-117, 1990) for the study of semigroup rings of inverse semigroups. Restriction, weakly ample and ample semigroups are considered.